Diagnostic accuracy of Cancer Antigen 125 (CA125) for endometriosis in symptomatic women: A multi-center study. (March 2017) - Hirsch, Martin; Duffy, James M.N.; Deguara, Christine S.; Davis, Colin J.; Khan, Khalid S.
Abstract: Study objective: To assess the diagnostic accuracy of serum Cancer Antigen 125 (CA 125) ≥ 30 units/milliliter (u/ml) for diagnosing endometriosis in symptomatic women. Study design: Prospective observational cohort study including patients with symptoms of pelvic pain or subfertility undergoing elective diagnostic laparoscopy at two tertiary referral hospitals. We excluded patients suspected to have other gynecological pathology. We evaluated the accuracy of serum CA 125 (index test) with histologically confirmed endometriosis (reference standard). Main results: Fifty-eight consecutive women recruited between October 2013 to March 2015. Women with endometriosis had a higher CA 125 level than those without endometriosis (mean 54.7 +/−71.6 vs 16.2 +/− 8.0). The specificity of CA 125 ≥ 30 u/ml was 96% (95% CI 81.7–99.9%) and sensitivity was 57% (95% CI 37.4–74.5%). The positive likelihood ratio for the histological presence of endometriosis with a CA 125 ≥ 30 u/ml was 15.8 (95% CI 2.3-112) providing a post-test probability of 94% (95% CI 71%–99%) in women with pelvic pain or subfertility. The area under the curve, 0.85 (95% CI 0.74–0.96) indicates high test accuracy. Conclusions: CA 125 ≥ 30 u/ml is highly predictive of endometriosis in women with symptoms of pain and/or subfertility. CA 125 should be considered as a rule-in test for expediting the diagnosis and management of endometriosis, CA 125 <30 u/ml is, however, unable to rule out endometriosis.